The Interplay Between Bone and Glucose Metabolism - Cipriani, Cristiana; Colangelo, Luciano; Santori, Rachele; Renella, Mario; Mastrantonio, Monia; Minisola, Salvatore; Pepe, Jessica (Frontiers in Endocrinology, 2020)
The multiple endocrine functions of bone other than those related to mineral metabolism, as regulation of insulin sensitivity, glucose homeostasis and energy metabolism have recently been discovered. In vitro and murine studies investigated the actions of several molecules derived from osteoblasts and osteocytes on glucose metabolism. In addiction, the effect of glucose on bone cells suggested a mutual cross-talk between bone and glucose homeostasis. In humans, these mechanisms are the pivotal determinant of the skeletal fragility associated with both type 1 and type 2 diabetes. Metabolic abnormalities associated with diabetes, as increase in adipose tissue and reduction of lean mass, effects of hyperglycemia per se, production of the advanced glycation end products, diabetes-associated chronic kidney disease, and perturbation of the calcium-PTH-vitamin D metabolism are of the main mechanisms involved. Finally, there have been multiple reports of antidiabetic drugs affecting the skeleton, with differences among basic and clinical research data, as well as of anti-osteoporosis medication influencing glucose metabolism. This review focuses on the aspects linking glucose and bone metabolism by offering insight into the most recent evidence in humans.